2019
DOI: 10.5935/0103-507x.20190015
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of conditions for apnea testing in a hypoxemic brain dead patient

Abstract: We report the case of a patient in whom brain death was suspected and associated with atelectasis and moderate to severe hypoxemia even though the patient was subjected to protective ventilation, a closed tracheal suction system, positive end-expiratory pressure, and recruitment maneuvers. Faced with the failure to obtain an adequate partial pressure of oxygen for the apnea test, we elected to place the patient in a prone position, use higher positive end-expiratory pressure, perform a new recruitment maneuver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Other, single case modifications aimed at improved oxygenation and/or ability to conduct and complete AT described a pre-AT recruitment maneuver with incremental titration of PEEP and maintenance of PEEP via a CPAP valve [30], prolonged AT for 110 min due to suspected cardiac ventilations resulting in a very slow increase in carbon dioxide levels [31] and successful use of prone positioning with CPAP and T-piece in a severely hypoxic patient [32].…”
Section: Augmentation Of Oxygenationmentioning
confidence: 99%
“…Other, single case modifications aimed at improved oxygenation and/or ability to conduct and complete AT described a pre-AT recruitment maneuver with incremental titration of PEEP and maintenance of PEEP via a CPAP valve [30], prolonged AT for 110 min due to suspected cardiac ventilations resulting in a very slow increase in carbon dioxide levels [31] and successful use of prone positioning with CPAP and T-piece in a severely hypoxic patient [32].…”
Section: Augmentation Of Oxygenationmentioning
confidence: 99%
“…( 10 ) Recently, a case was reported that showed the possibility of performing the apnea test in a prone position and with the CPAP valve coupled to a T-piece. ( 11 )…”
Section: Discussionmentioning
confidence: 99%
“…Additionally to providing safety to patients with hypoxic respiratory failure, the apnea test with CPAP is being used as part of a lung preservation strategy for transplantation and includes a tidal volume of 6 to 8mL/kg and a PEEP of 8 to 10cmH 2 O, in addition to alveolar recruitment maneuvers. ( 13 - 15 ) Although recruitment maneuvers ( 8 , 11 , 13 - 15 ) are suggested by some studies, their potential complications must be considered, such as hypotension, decreased SaO 2 , arrhythmias and barotrauma. Also, maintenance of the FRV promoted by CPAP is likely sufficient to maintain oxygenation.…”
Section: Discussionmentioning
confidence: 99%